Whole body sodium depletion modifies AT1 mRNA expression and serotonin content in the dorsal raphe nucleus. (1st April 2019) - Porcari, Cintia Yamila; Araujo, Iracema Gomes; Urzedo‐Rodrigues, Lilia; De Luca, Laurival Antonio; Menani, José Vanderlei; Caeiro, Ximena Elizabeth; Imboden, Hans; Antunes‐Rodrigues, José; Reis, Luís Carlos; Vivas, Laura; Godino, Andrea; Mecawi, André Souza
Abstract : Angiotensin II (Ang II) acts on Ang II type 1 (AT1) receptors located in the organum vasculosum and subfornical organ (SFO) of the lamina terminalis as a main facilitatory mechanism of sodium appetite. The brain serotonin (5‐HT) system with soma located in the dorsal raphe nucleus (DRN) provides a main inhibitory mechanism. In the present study, we first investigated the existence of Ang II AT1 receptors in serotonergic DRN neurones. Then, we examined whether whole body sodium depletion affects the gene expression of the AT1a receptor subtype and the presumed functional significance of AT1 receptors. Using confocal microscopy, we found that tryptophan hydroxylase‐2 and serotonin neurones express AT1 receptors in the DRN. Immunofluorescence quantification showed a significant reduction in 5‐HT content but no change in AT1 receptor expression or AT1/5‐HT colocalisation in the DRN after sodium depletion. Whole body sodium depletion also significantly increased Agtr1a mRNA expression in the SFO and DRN. Oral treatment with the AT1 receptor antagonist losartan reversed the changes in Agtr1a expression in the SFO but not the DRN. Losartan injection into either the DRN or the mesencephalic aqueduct had no influence on sodium depletion‐induced 0.3 mol L ‐1 NaCl intake. The results indicate the expression of Agtr1a mRNA in the DRN and SFO as a marker of sodium depletion. They also suggest that serotonergic DRN neurones are targets for Ang II. However, the function of their AT1 receptors remains elusive.